Savings in Isolation and Under a Collective Decision Rule - Wellisz, Stanislaw (Quarterly Journal of Economics, 1977)
Journal Article Savings in Isolation and Under A Collective Decision Rule Get access Stanislaw Wellisz Stanislaw Wellisz Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 91, Issue 4, November 1977, Pages 663–666, https://doi.org/10.2307/1885888 Published: 01 November 1977